The governmentality of tropical forests and sustainable food systems, and possibilities for post-2020 sustainability governance. Issue 1 (2nd January 2023) - Smallwood, J. Miller; Delabre, I.; Pinheiro Vergara, S.; Rowhani, P.
ABSTRACT: Continued conversion of tropical forests to agriculture risks jeopardising planetary integrity. The UN Sustainable Development Goal (SDG) targets to halt deforestation by 2020, alongside other global measures for zero deforestation, were not achieved. Applying a governmentality lens, we aim to better understand global governance mechanisms for tropical forests and sustainable food systems, and identify opportunities to improve them post 2020. We rely on data from global measures, institutions, and interviews with public and private actors working on tropical forest and food policy to undertake a discourse analysis of the (i) SDGs and other global measures on forests and food systems, (ii) contexts of the institutions studied, and (iii) implementation of global measures relating to forests and sustainable food systems. Our analysis reveals six discursive themes: (1) Policy framing of tropical forests – a token effort (2) Deceptive interlinkages, (3) Participation of the usual suspects, (4) Insufficient stakeholder representation, (5) Cleaning up supply chains and, (6) A green recovery. The themes show how the promotion and reproduction of neoliberal values of tropical forests consistently inhibit conservation, negatively impacting on planetary integrity. We identify opportunities to shift towards a new governmentality for informing international efforts on tackling tropical deforestation post-2020.